Implementation Of Carbon Tax as an Effort to Improve The Economy and Preserve The Environment - Endang Mahpudin; Yuniar Rahmatiar; Muhamad Abas (Journal of Law, Politic and Humanities, 2026)
Climate change has become a global challenge that needs to be addressed together. Indonesia is one of the countries that is vulnerable to climate change. The decline in environmental quality that has an impact on natural disasters can be detrimental to various parties. In Indonesia, Law Number 32 of 2009 concerning Protection and Management of the Environment has been enacted, which contains systematic and integrated efforts to preserve the environment and as an effort to prevent pollution and/or environmental damage. In addition, regulations have also been issued on carbon taxes in Article 13 of Law Number 7 of 2021 concerning Harmonization of Tax Regulations. The main objective of the carbon tax is to change the behavior of economic actors to switch to low-carbon economic activities, but the implementation of the carbon tax is currently still being postponed. The research methodology is a literature review, in the form of normative legal, qualitative. The data presented are secondary data obtained from various literature sources. This study concludes that in order to reduce the worsening environmental damage and also increase revenue from the Tax sector, it is necessary to implement a Carbon Tax, but the Law that has been issued has been postponed, with various considerations, so that the carbon tax can be implemented and run effectively, there is a need for improved regulations that not only function as economic tools, but also as drivers of behavioral change and technological development to achieve sustainability goals.